Hispanic serving institutions (HSIs) in practice : defining "servingness" at HSIs - Garcia, Gina Ann, 1978- (Hispanics in education and administration., 2020)
"As the general population of Latinxs in the United States burgeons, so does the population of college-going Latinx students. With more Latinxs entering college, the number of Hispanic-Serving Institutions (HSIs), which are not-for-profit, degree granting postsecondary institutions that enroll at least 25% Latinxs, also grows, with 523 institutions now meeting the enrollment threshold to become HSIs. But as they increase in number, the question remains: What does it mean to serve Latinx students? This edited book, Hispanic Serving Institutions (HSIs) in Practice: Defining "Servingness" at HSIs, fills an important gap in the literature. It features the stories of faculty, staff, and administrators who are defining "servingness" in practice at HSIs. Servingness is conceptualized as the ability of HSIs to enroll and educate Latinx students through a culturally enhancing approach that centers Latinx ways of knowing and being, with the goal of providing transformative experiences that lead to both academic and non-academic outcomes. In this book, practitioners tell their stories of success in defining servingness at HSIs. Specifically, they provide empirical and practical evidence of the results and outcomes of federally funded HSI grants, including those funded by Department of Education Title III and V grants. This edited book is ideal for higher education practitioners and scholars searching for best practices for HSIs in the United States. Administrators at HSIs, including presidents, provosts, deans, and boards of trustees, will find the book useful as they seek out ways to effectively serve Latinx and other minoritized students. Faculty who teach in higher education graduate programs can use the book to highlight practitioner engaged scholarship. Legislators and policy advocates, who fight for funding and support for HSIs at the federal level, can use the book to inform and shape a research-based Latinx educational policy agenda. The book is essential as it provides a framework that simplifies the complex phenomenon known as servingness. As HSIs become more significant in the U.S. higher education landscape, books that provide empirically based, practical examples of servingness are necessary"--